If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 = 4 + v Solving -12 = 4 + v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-1v' to each side of the equation. -12 + -1v = 4 + v + -1v Combine like terms: v + -1v = 0 -12 + -1v = 4 + 0 -12 + -1v = 4 Add '12' to each side of the equation. -12 + 12 + -1v = 4 + 12 Combine like terms: -12 + 12 = 0 0 + -1v = 4 + 12 -1v = 4 + 12 Combine like terms: 4 + 12 = 16 -1v = 16 Divide each side by '-1'. v = -16 Simplifying v = -16
| 3(2w-4)=18 | | 3x+9=8x-6 | | -4y+9+y=3 | | 2[A+5]=2[2A+3] | | 3x+2y=52 | | 6z=-14 | | 5x-7=15+3x | | 2(x-1)(x+1)=2 | | 5a-(2a-1)=2 | | 5(p+6)=9p | | 2[4M-5]=4M+2 | | x^2+9-9-6x+6x=0 | | x^2+9-6x+6x=0 | | 4[X-3]=3[3X+1] | | x^2+9+6x=0 | | x^2+9-9+6x=0 | | 4x-2=x | | 2[a+5]=2[2A+4] | | 3x+9=8x-3 | | -45=3(4v+1) | | T-9=-5 | | 3+x=5+4x | | 3[x-2]=5[x+4] | | 4x/4=9/4 | | 5b-4=6[b+2] | | -2y+4(-3v-4)=-58 | | -6n-4=4-5n | | -6n-4=4-5n | | -6n-4=4-5n | | 5[x-2]=2x-13 | | -3(4m+6)=3(4-2m) | | -3(4m+6)=3(4-m) |